Persepsi Pemimpin Redaksi Media Massa di Surabaya Tentang Kebebasan Pers di Era Kepemimpinan Presiden Joko Widodo - Wati, Leni Setya; Sari, Ratna Puspita (LPPM Stikosa-AWS, 2024)
Freedom of the press is a hope for media workers so that they can carry out their duties and functions as journalists in accordance with the state mandate in the press law. However, the cases of violence that still occur against journalists and the democracy and press freedom index data which has decreased over the last decade, reaching 6.3 in 2020, is one of the facts that this freedom is still not felt by journalists, therefore Researchers are interested in researching press freedom in the Jokowi era. The method used in this research is descriptive qualitative using Alfred Schutz's phenomenological theory which divides into three important aspects in constructing meaning from social reality or phenomena that occur, namely the understanding aspect, the experience aspect, and the meaning aspect. The informants in this research were four Chief Editors of mass media in Surabaya who had been certified by the Press Council. From the results of research conducted with four informants, what they felt about press freedom in the era of President Jokowi's leadership was that Jokowi was no longer treating critical media in coercive ways, with power, with threats or with political pressure such as previous eras but by utilizing the media business in this era which is controlled by the market as one of the ways the government uses to weaken media that are critical of the government, namely by limiting the economic access they will get.